2015
DOI: 10.3892/mmr.2015.3149
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II promotes differentiation of mouse c-kit-positive cardiac stem cells into pacemaker-like cells

Abstract: Cardiac stem cells (CSCs) can differentiate into cardiac muscle-like cells; however, it remains unknown whether CSCs may possess the ability to differentiate into pacemaker cells. The aim of the present study was to determine whether angiotensin II (Ang II) could promote the specialization of CSCs into pacemaker-like cells. Mouse CSCs were treated with Ang II from day 3–5, after cell sorting. The differentiation potential of the cells was then analyzed by morphological analysis, flow cytometry, reverse transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The immunofluorescence analysis demonstrated that a small number of cells co-expressed c-kit and nanog, results which were concordant with those of our previous studies ( 32 , 33 ). Heart failure not only severely damages the heart muscle cells, it also reduces the number of c-kit-positive cells, nanog-positive cells and stem cells ( 34 , 35 ).…”
Section: Discussionsupporting
confidence: 92%
“…The immunofluorescence analysis demonstrated that a small number of cells co-expressed c-kit and nanog, results which were concordant with those of our previous studies ( 32 , 33 ). Heart failure not only severely damages the heart muscle cells, it also reduces the number of c-kit-positive cells, nanog-positive cells and stem cells ( 34 , 35 ).…”
Section: Discussionsupporting
confidence: 92%
“…Ang II has been widely used as an inducer to stimulate the differentiation of MSCs to functional cells such as cardiomyocytes, endothelial cells, adipocytes, and smooth muscle-like cells [1216]. The doses of Ang II usually used to stimulate differentiation of MSCs were from 0.1 μ M to 10 μ M [1214].…”
Section: Introductionmentioning
confidence: 99%
“…74 Stem cells that engraft functionality and differentiations, as well as the embryonic stage differentiation of the progenitor cells, are affected by the RAS. 75 In addition to influencing cellular function and structure in the adult pancreas, local RAS has a major effect on pancreatic stem cells/ progenitor cells (PPC) during development. 1 Pancreatic islet RAS regulates PPC differentiation, after transplantation of MSCs, and thereby enables beneficial outcomes to accomplish permanent normal blood glucose levels in patients with Type 1 diabetes.…”
Section: The Role Of Ras In Stem Cellsmentioning
confidence: 99%